The effectiveness of practical work on students’ motivation and understanding towards learning physics - Mei, Chi Lee (2018)
The study aimed to synthesis polyphenol glycoside through enzymatic transglycosylation reaction using cyclodextringlucanotransferase (CGTase) derived from culture of Trichoderma viride in the present of polyphenolic extract ofMoringa oleifera to evaluate its antioxidant activities of the polyphenol glycoside as transglycosylation product.Chemical structures of the enzymatically synthesized product were identified using nuclear magnetic resonance (1HNMR and 13C NMR) spectroscopy as gallic acid-4-O-ß-glucopyranoside (GAGP), ellagic acid-4-O-ß-glucopyranoside (EAGP), and catechin-4’-O-glucopyranoside (CGP), respectively. The EAGP was furthermore applied to investigate its effect on hypolipidemic and antidiabetic activity in normal and alloxan-induced diabetic rats. Blood glucose levels weremeasured significantly (p<0.05) increasing in all diabetic rats as compared to normal control rats. Three differentdosages of EAGP showed significantly decreasing (p<0.05) blood glucose levels of the diabetic rats as compared tountreated diabetic group. All diabetic groups presented significantly lower body weight as compared to normal rats as control. The diabetic groups administered with different dosages of EAGP showed improvement in weight gain ascompared to untreated diabetic group. All the hyperglycemic groups which were treated with EAGP recorded lower biochemical parameters of blood serum as compared to untreated diabetic group.